O Sermão da Sexagésima: uma arena de vozes - Oliveira, Lucimara de (2008)
The aim of this work is to analyze Padre Antônio Vieira's Sermão da Sexagésima in its compositional form, style and theme (Bakhtin 1979/2003), and also the interdiscourses that compose it so as to identify how the sermon genre was conceived by the jesuit in his socio-historical context. We believe that studying the Sermão da Sexagésima means to identify its discourse's modernity, update it and assess it in a different situation which can contribute for discourse analysis's studies and for teachers who have to motivate high school students to read and understand Vieira's work. For the Sermão da Sexagésima's analysis we take as theoretical perspective the bakhtinian notion of discursive genres and the presence of the other's discourse (Bakhtin 1929/2004; 1979/2003). We follow Bakhtin and his circle's ideas for language studies, under a socio-historical perspective. Hence, we will recover this sermon's circulation sphere in relation to its sociohistorical context, its interlocutors and its aim, relating it to Vieira's contribution to sermons in terms of a discursive genre. Therefore, we will investigate Vieira's updating process for this kind of genre